Individualized and controlled laser beam pretreatment process for adhesive bonding of fiber-reinforced plastics—Part I: Optical detection of impurities on the component surface. (October 2020) - Weiland, J; Kunze, B; Dittmar, H; Marx, B; Schiebahn, A; Jäschke, P; Overmeyer, L; Reisgen, U
This paper deals with the detection and localization of impurities such as release agent residues and fingerprints on fiber-reinforced plastic surfaces in an inline process step. This information can be used to carry out a locally individual and controlled surface pretreatment using laser radiation in order to improve the adhesion conditions. In this paper, surfaces from polyamide 6 reinforced with glass fiber are considered. To detect the impurities, inline images of the joining surfaces are taken using a laser line triangulation system. These image data are then examined with a specially developed algorithm of digital image processing. The real-time algorithm is based on the method of material-specific threshold values. In addition to real impurities, the algorithm was validated with artificial impurities. The central result of this work is the detection and local impurities of release agent residues and fingerprints down to a detail size of 0.3 mm.